MODERN ERA OF HUMAN RESOURCE MANAGEMENT:A STRATEGIC EDGE TO HUMAN TALENT MANAGEMENT - Dr.Aajaz Ahmad Hajam; Alphonsa S John (RADJA PUBLIKA, 2023)
Increasing theoretical and conceptual understanding of human talent management (HTM) is the aim of this research. To clarify the important connections between competency emphasis, talent pooling, talent investment, and talenting orientation and value generation, authors have put out a conceptual framework and a few propositions. A human talent management model has been presented by the authors, which could help academics and practitioners alike better comprehend the talent management orientation. Also, using this approach, practitioners may be able to intelligently match talent strategies with company objectives to produce higher economic value (Shareholders, Employees, Owners, Customers, agents, and other stakeholders).